2010
DOI: 10.14569/ijacsa.2010.010107
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency Identification Based Library Management System

Abstract: Abstract-Radio frequency identification (RFID) is a term that is used to describe a system that transfers the identity of an object or person wirelessly, using radio waves. It falls under the category of automatic identification technologies. This paper proposes RFID Based Library Management System that would allow fast transaction flow and will make easy to handle the issue and return of books from the library without much intervention of manual book keeping. The proposed system is based on RFID readers and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A radio frequency identification is a computing technique based on the use of radio waves for transmitting and receiving data between a reader and movable item to identify, categorize and track wirelessly [10]. It facilitates the library transactions with the help of RFID modules without human (manual) typing, provides a monitoring module and increase security.…”
Section: Rfid In the Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…A radio frequency identification is a computing technique based on the use of radio waves for transmitting and receiving data between a reader and movable item to identify, categorize and track wirelessly [10]. It facilitates the library transactions with the help of RFID modules without human (manual) typing, provides a monitoring module and increase security.…”
Section: Rfid In the Librarymentioning
confidence: 99%
“…The measurement and identification of vulnerabilities in existing systems has been done first then collection of requirements of the new system. A radio frequency identification is a computing advanced technique able to transmit and receive data between a reader and movable item to identify, categorize and track wirelessly [10]. The previous study demonstrated that RFID even brought remarkable advantage, cannot be used for record and become incompatible when tags or labels have been removed on targeted objects reason why CCTV become more advantage.…”
Section: Book Borrow Modulementioning
confidence: 99%
“…Grover & Ahuja 4 found that the efficiency of the RFID-LMS system depends upon the information written in tags and to yield better performance, good quality of RFID readers and RFID tags should be used.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This technique has been increased in many fields like industry, business, food and library management, and so on [1]. In wireless communications, the RFID systems are one of the most promising technologies [2] that emerged after automatic identification to detect any object anywhere [3], [4].…”
Section: Introductionmentioning
confidence: 99%